ANALISIS PENGARUH PRESTASI KERJA PEGAWAI TETAP TERHADAP PROMOSI JABATAN PADA PT. PLN (PERSERO) AREA BANJARMASIN - Diana Hayati; Mailiana - (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2015)
Abstract, This research aimed analyse the Influence of Labour Capacity of Jobholder to Position/Occupation Promotion of at PT. PLN (Persero) accurate by Area Banjarmasin. The labour capacity in the form of quality work, amount work, attitude work and reliability of either through simultan and parsial to promotion of jobholder position and also dominant variable among/between quality work the, amount work the, attitude work and reliability to promotion of jobholder position. Research population is jobholder of PT.PLN (Persero) Area Banjarmasin. Technique of withdrawal sampel use the method of purposive sampling. Sum up the sampel in this research is 53 jobholder. Research method used descriptive and verifikatif. Method analyse the data used in this research is doubled linear analysis regresi in the form of test kuesionoer that is test the validity and test the realibility and also test the hypothesizing that is test the F and test the T. The results found that the t-test the quality of work by 1,998 bigger than t table is 1,667, which means a significant effect on employment promotion. The quantity of work shows the t-count equal to 0.665 is smaller than t-table is 1,667, which means no significant effect on employment promotion. Work attitude shows the t-count of 1,148 is smaller than t-table is 1,667, which means no significant effect on employment promotion. Reliability indicates the t-count of 1,347 is smaller than t-table is 1,667, which means no significant effect on employment promotion. F-test results showed F count of 5,154 is greater than F of the table is 2,793.